2004
DOI: 10.1007/s00432-003-0498-7
|View full text |Cite
|
Sign up to set email alerts
|

The current and future role of dexrazoxane as a cardioprotectant in anthracycline treatment: expert�panel�review

Abstract: This article summarizes the views of an expert meeting of cardiologists and oncologists on the use of dexrazoxane in anthracycline-based chemotherapy. Anthracycline-induced cardiotoxicity remains a major concern and new trends in treatment (e.g., combination of an anthracycline with other agents) will ensure that it remains a problem. Dexrazoxane reduces this cardiotoxicity in adults and children with a range of tumor types. Further research may help to identify those patients who are at particular risk of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(84 citation statements)
references
References 31 publications
1
79
1
2
Order By: Relevance
“…85 Dexrazoxane consistently reduces the cardiotoxic effects of anthracyclines, allowing higher anthracycline doses to be used safely. 86 Complete protection, however, could not be achieved in most of the studies, and it is not known yet whether dexrazoxane provides any protection against late cardiovascular effects. Importantly, the weight of evidence shows that dexrazoxane does not affect the antitumor activity of anthracyclines.…”
Section: Previous Anthracycline Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…85 Dexrazoxane consistently reduces the cardiotoxic effects of anthracyclines, allowing higher anthracycline doses to be used safely. 86 Complete protection, however, could not be achieved in most of the studies, and it is not known yet whether dexrazoxane provides any protection against late cardiovascular effects. Importantly, the weight of evidence shows that dexrazoxane does not affect the antitumor activity of anthracyclines.…”
Section: Previous Anthracycline Exposurementioning
confidence: 99%
“…Importantly, the weight of evidence shows that dexrazoxane does not affect the antitumor activity of anthracyclines. 86 Another strategy is the development of liposomal drug formulations of the anthracyclines. Liposomal encapsulation alters the tissue distribution of anthracyclines: tissues with a sinusoidal capillary system preferentially take up liposomes, so the continuous capillaries of cardiac muscles would reduce heart exposure to the drug.…”
Section: Previous Anthracycline Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The cytoprotective effects of dexrazoxane, in the presence of doxorubicin, have been well established in animal species (11) and hu- mans (12). Furthermore, clinical trials have revealed that the cytoprotection of dexrazoxane does not interfere with the anti-tumor effects of doxorubicin, and therefore to this day dexrazoxane serves as one of the best cytoprotective drugs against doxorubicin (13). The hydroxyl radical that makes up the ROS is a highly reactive species that can cause lipid peroxidation, oxidative damage to DNA, and eventual cell death (14).…”
Section: Cytoprotective Effects Of Dexrazoxane Losartan and Diltiazementioning
confidence: 99%
“…Multiple other randomized trials and a pooled analysis have not confirmed these findings [7,12,17,[21][22][23][24]26]. However, these studies enrolled mainly patients with solid tumors; the majority of them are adults with advanced breast cancer.…”
mentioning
confidence: 96%